In vitro evaluation of bio-fortification effects on the nutritional quality, toxicological safety, and antioxidant of cassava (Manihot esculenta) flour, and environmental safety of processing water, using natural additives - Albishi, Tasahil S.; Adaigho, D.; Alqahtani, Nashi K.; Sami, Rokayya; Uguru, Hilary; Helal, Mahmoud; Alaoufi, Shatha H.; Alkaltham, Mohammed Saeed; Osiga-Aibangbee, D.; Okolotu, G. I.; Emumejaye, E. P.; Qari, Sameer H. (Frontiers in Nutrition, 2026)
The impact of bio-fortification on the nutritional quality, anti-nutritional factors, glycemic indices, and toxicological effects of cassava (Manihot esculenta) flour (CF), was investigated in vitro in this scientific research. The cassava roots were administered with, eleven distinct treatment strategies (F1 to F11), formulated from Moringa oleífera leaves, Syzygium aromaticum seeds, and Curcuma longa rhizomes derivatives. Additionally, two control units were used: Control A, which consisted of unsoaked cassava roots; and Control B (the vehicle control), which involved soaking the cassava roots in untreated tap water. All the laboratory tests were conducted in accordance with standard procedures. The experimental outcomes indicated that, the treatments significantly impacted the physicochemical and biological properties of the CF, and the soaking water (p ≤ 0.05). Especially, the treatments contribute intensely to the CF antioxidant activity, and health safety of the fortified flour. It was observed that, the hybridized treatments resulted in a 69.76% reduction in the HCN levels, and a 51.28% reduction in the GI levels in the CF, respectively. Also, the treatments initiated nutrients infusion into the enriched CF, as the carotenoid level increased from 0.47 to 1.80 mg/100 g; protein content increased from 1.34 to 1.99%; carbohydrate content increased from 74.33 to 84.33 g/100 g DW; and B vitamin content increased from 0.37 to 0.87 mg/100 g DW. Though, the Control A flour contained appreciable essential nutrients contents, its high glycemic index potential (78), and hydrogen cyanide level (0.43 mg/100g DW), increases its health risk. Notably, the treatment resulted in 31.11% reduction in the total bacterial counts, of the soaking water, as well as a biodegradation of the toxic metals (Cd, Cr, As, and Pb) in the enriched flour. Particularly, the methodological approach adopted in this research will facilitate high eco-friendly cassava flour production, as well as the utilization of cheap and readily available bio-additives.